2010
DOI: 10.1007/s00134-010-2094-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between altered small intestinal motility and absorption after abdominal aortic aneurysm repair

Abstract: Whilst disruption in SI motility and flow (impedance) events was associated with reduced absorption of both lipid and carbohydrate, lipid malabsorption was more prolonged. This may reflect inadequate mixing of chyme from altered motility, so varying the nutrient composition of enteral feed may improve absorption in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
(65 reference statements)
0
14
0
Order By: Relevance
“…Although absorption of both lipid and glucose were impaired immediately after the surgical repair of an abdominal aortic aneurysm, which was associated with disruption of small intestinal motility [43], the lipid malabsorption persisted even when glucose absorption and intestinal motor function had normalized. Although absorption of both lipid and glucose were impaired immediately after the surgical repair of an abdominal aortic aneurysm, which was associated with disruption of small intestinal motility [43], the lipid malabsorption persisted even when glucose absorption and intestinal motor function had normalized.…”
Section: Intestinal Malabsorptionmentioning
confidence: 99%
“…Although absorption of both lipid and glucose were impaired immediately after the surgical repair of an abdominal aortic aneurysm, which was associated with disruption of small intestinal motility [43], the lipid malabsorption persisted even when glucose absorption and intestinal motor function had normalized. Although absorption of both lipid and glucose were impaired immediately after the surgical repair of an abdominal aortic aneurysm, which was associated with disruption of small intestinal motility [43], the lipid malabsorption persisted even when glucose absorption and intestinal motor function had normalized.…”
Section: Intestinal Malabsorptionmentioning
confidence: 99%
“…Nguyen et al . [34] have investigated the absorption of fat and carbohydrates in the small intestine in relation to motility following surgical repair of abdominal aortic aneurysms. Motility was impaired as compared to controls.…”
Section: Nutrition and Therapeuticsmentioning
confidence: 99%
“…Small intestinal motility was not measured in this study; however, our group has previously shown the detrimental effects of critical illness on gastrointestinal motility and luminal flow (30)(31)(32). These findings suggest that factors such as reduced activity of sucrase, inadequate nutrient exposure to the luminal mucosa due to alterations in small intestinal motility or morphology, and reduced uptake in portal blood due to reduced mesenteric flow may play an important role in the absorption and metabolism of sucrose during critical illness.…”
Section: Discussionmentioning
confidence: 73%
“…We have previously demonstrated impaired absorption of glucose (9,29,30, 35) (a monosaccharide) and triglycéride (30). We have previously demonstrated impaired absorption of glucose (9,29,30, 35) (a monosaccharide) and triglycéride (30).…”
Section: Discussionmentioning
confidence: 93%